73 Development of a cloud-based device management application for simple allocation and tracking of devices and equipment. (22nd November 2019) - Berry, Wilfrid; Garcia-Escudero, Cecilia Pretus; Taneli, Poyzan; Bassi, Daiana; Conner, Sue; Fu, Yun; Mohamedally, Dean; Molyneux, Gemma; Roberts, Graham; Sebire, Neil
Abstract : Introduction: Keeping track of devices across large organisations can be challenging. Hospitals contain many electronic devices and pieces of equipment that can be moved around the building and lost. The aim of this project was to develop an electronic system for the management of devices with an app to allow for devices to be loaned to named individuals. Method: As part of a joint collaboration between GOSH and UCL computer science (CS) through the industry exchange network programme, CS students devised a platform for quickly and easily logging and tracking devise, using GOSHDRIVE as a model. The application employs a 3-tier, presentation, logic and data, software architecture pattern. The presentation tier consists of a mobile application and web app. The mobile application was developed in Ionic4, an open source, cross-platform toolkit for developing mobile and desktop apps that uses standard web technologies; HTML, CSS and JavaScript. The web app make use of Bootstrap to create fully responsive web pages. The logic tier, which contains the application's functional business logic, was written in PHP and consists of the RESTful APIs the mobile and web app use to access the data. The data tier comprises of a MySQL database to store a list of devices, loans and borrowers details. Results: A web user interface was developed to allow administrators to create a database of equipment owned by an organisation with descriptions, serial numbers and physical locations. Each piece of equipment logged is assigned a QR code that can easily be scanned to check items in or out of the department. Additionally, lost items can be scanned and returned to the correct location. Conclusion: This application and web interface allows assets to be catalogued and loaned. This represents a low cost way of maintaining records of equipment and devices across a large organisation.